Antioxidant Activity Testing Combination of Moringa Leaf (Moringa oleifera L.) and Bambian (Ocimum sanctum L.) Leaves Extract Using DPPH Method - Endah Dwijayanti; Masli Nurcahya Zoraida; Siti Rahayu Kurnianingsih (Department of Chemistry - Universitas Bangka Belitung, 2023)
Research on the antioxidant activity combination of the ethanol extract of Moringa (Moringa oleifera L.) and basil (Ocimim sanctum L.) leaves has been carried out. The purpose of this study was to identify the content of secondary metabolites and measure the value of antioxidant activity as well as the maximum ratio of the combination of ethanol extract of Moringa leaves and basil leaves. The research methods include maceration extraction using 70% ethanol as a solvent, phytochemical screening using specific reagents and antioxidant activity testing using the DPPH method. The results of the phytochemical screening test for Moringa leaf extract and basil leaves were positive for containing chemical compounds of the flavonoid and tannin groups. The antioxidant activity test of Moringa leaf ethanol extract obtained IC50 results of 69.474 ppm which was categorized as a strong antioxidant, while basil leaves of 34.663 ppm which was categorized as very strong antioxidant, while the results of the combined study of antioxidant activity test of Moringa leaf ethanol extract and basil leaves obtained IC50 results at the ratio of 25:25 mg is 51.589 ppm and the ratio of 35:15 mg is 57.009 ppm which was categorized as a strong antioxidant, while at 15:35 mg is the optimum ratio because the IC50 result is 42.714 ppm which was categorized as very strong.